Blazing Ballet Girls and Flannelette Shrouds: Fabric, Fire, and Fear in the Long Nineteenth Century. (3rd May 2016) - Matthews David, Alison
Abstract: Fire was one of the most terrifying dangers for women and children in the nineteenth century. Many burned to death in highly inflammable clothing. A new, sylph-like Romantic feminine ideal in dress arose in tandem with the gas lighting that illuminated the light white cottons and almost "immaterial" materials that became fashionable during the Neoclassical period. These textiles included machine-woven gauze, tulle, and tarlatane, and they put working-class ballet dancers pirouetting near gas footlamps at particular risk. French prima ballerina Emma Livry died when her tutu caught on fire, and the charred remains of her costume are still preserved at the Musée-bibliothèque de l'Opéra in Paris. In the late 1870s, another popular, mass-produced fabric, flannelette, was sold as a cheap, washable substitute for woolen flannel. Yet the soft, raised, furry "nap" of the fabric that kept children warm set them ablaze because most working-class homes lacked proper fire guards. In response to the dangers ushered in by these new products, textile manufacturers and chemists attempted to flameproof them, but these fireproofed fabrics were not widely adopted. This article maps emotional responses to clothing accidents, tracing a shift from the romantic individualization of early nineteenth-century fire deaths to the anonymous statistical analysis and detached scientific observation of accidents in the late nineteenth century. It considers the role of the researcher's and curator's own emotional reactions to the material remains of disturbing garments that still bear the traces of physical trauma in their very fibers.